Confronting risks at the intersection of climate change and artificial intelligence: The promise and perils of rights-based approaches - Barrie Sander (Netherlands Quarterly of Human Rights, 2025)
In a period of heightened societal expectations and investment in artificial intelligence (AI) technologies, this article directs attention towards the risks and concerns associated with relying on AI to address climate change. These include: AI's climate consumptionism in the form of its direct and indirect environmental footprint; AI's legitimation of techno-centric thinking within climate mitigation and adaptation initiatives; AI's entanglement in repressive practices of surveillance against climate activists and migrants; and AI's influence over public discourse in ways that undermine societal responsiveness to climate change. At a time when these risks are garnering greater public attention, this article assesses the promise and perils of rights-based approaches for addressing them. To this end, the article identifies three challenges that may inhibit the value of rights-based approaches at the intersection of climate and AI governance: first, the challenge of concretisation, encompassing difficulties translating the open-textured vocabulary of rights into more concrete operational standards that are attuned to the particularities of AI technologies; second, the challenge of individualism, encompassing difficulties of relying on the predominantly individualised discourse of rights to address the collective and societal concerns to which climate applications of AI give rise; and finally, the challenge of marketised managerialism, encompassing the challenge of guarding against corporate capture given the dominance of Big Tech companies in global AI supply chains. The article concludes that harnessing rights-based approaches requires being candid about their limitations, uncertainties, and perils – acknowledging rather than smoothing over the complexities and weaknesses of rights as a vocabulary for confronting risks and concerns at the intersection of climate change and AI.